Sex differences of visceral fat with cardiac structure and function in type 2 diabetes: A cross‐sectional study - Chen Rui‐hua; Lin Yi; Xu Huan‐bai; Wang Yu‐fan; Peng Yong‐de (Journal of Diabetes)
Abstract Background The aim of this study is to analyze the associations among fat distribution, left ventricular (LV) structure, and function in T2DM patients and further assess the sex differences among them. Methods Two thousand and one hundred seven T2DM patients were enrolled to this study. Patients' height, weight, BMI, visceral fat area (VFA), baPWV, parameters of cardiac structure and function, and clinical biochemical indicators were measured and collected. Results There were significant differences between male and female T2DM patients in age, duration of diabetes, complication ratio of hypertension and dyslipidemia, smoking history, visceral fat, baPWV, and ventricular structure and function (p < 0.05). Compared with the Q1 group, female patients in the highest quartile (Q4) of VFA had a decreased LVEF and significantly increased baPWV (p < 0.05), whereas no such changes were found in males. The correlation analysis showed that LVEF in male patients was negatively correlated with hypertension history, using of CCBs, GLP‐1RA, lipid‐lowering medications, BMI, WC, WHR, FPG, FC‐P, HbA1c, GA, HOMA‐IR, Cr, and baPWV, while the LVEF in female patients was negatively correlated with VFA, VSR, VFA/BMI, VFA/H2, VFA/weight in females (p < 0.05). LVMI was positively associated with diabetes duration, age, hypertension history, WC, WHR, VFA, SFA, VFA/BMI, VFA/H2, VFA/weight, and baPWV in both males and females. Multivariable‐adjusted linear regression analysis showed that VFA was independently associated with LVEF (β = − 0.096, p = 0.010), LVMI (β = 0.083, p = 0.038), and baPWV (β = 0.120, p = 0.003) in females. Conclusions Values of VFA were independently associated with LVEF, LVMI, and baPWV in women, but not in men, in patients with T2DM.